2021
DOI: 10.1186/s13046-021-01834-9
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic tumour cell-derived exosomal miR-340-5p promotes radioresistance of oesophageal squamous cell carcinoma via KLF10

Abstract: Background Radiotherapy resistance is a major obstacle in the treatment of oesophageal squamous cell carcinoma (OSCC). Hypoxia is a critical cause of radioresistance. However, the communication between hypoxic cells and aerobic cells via exosomes during the transfer of radiation resistance remains unclear. Methods Exo-miR-340-5p levels were analysed by RNA-seq and qRT-PCR. We co-cultured OSCC cells with isolated normoxic and hypoxic exosomes to stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 36 publications
(43 reference statements)
0
40
0
Order By: Relevance
“…γH2A is an established marker of DNA damage ( 23 ). Relative to mock-silenced cells, DCTPP1-deficient induced BRCA cells had significantly higher γH2A levels ( Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…γH2A is an established marker of DNA damage ( 23 ). Relative to mock-silenced cells, DCTPP1-deficient induced BRCA cells had significantly higher γH2A levels ( Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…Then, cultured for 2 weeks later, 1% crystal violet was applied in staining clonogenic cells. The clonogenic survival curves were generated according to the following formula model: SF = 1 − (1 − e −kd ) n as previously described [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The immunofluorescence of γ H2AX was detected by the anti- γ H2AX primary antibody (1 : 500, Abcam, UK) and the detailed process was described in the previous protocol [ 17 ]. Cells were snapped under a confocal fluorescence microscope (Leica).…”
Section: Methodsmentioning
confidence: 99%
“… 40 Recently, it has been shown that hypoxic tumor cell-derived exosomal miR-340-5p conferred radioresistance in ESCC by targeting kruppel-like factor 10 (KLF10)/UV radiation resistance-associated gene protein (UVRAG). 57 The level of miR-340-5p in the plasma exosomes was closely related to radiotherapy response and prognosis. miR-340-5p might be a therapeutic target for overcoming radioresistance in ESCC.…”
Section: Exosomes Promote Ec Therapy-resistancementioning
confidence: 99%
“… 70 In addition, circulatory exosomal miR-340-5p and miR-339-5p might be promising biomarkers for prediction of radiotherapy response and prognosis in patients with ESCC. 57 , 58 Exosomal miRNAs will have great potential application in tumor individualized treatment.…”
Section: Exosomal Mirnasmentioning
confidence: 99%